Inhibition of the polyol pathway by Ducrosia anethifolia extract: plausible implications for diabetic retinopathy treatment - Saheem Ahmad; Mohammad Faizan Ali Ahmad; Saif Khan; Sultan Alouffi; Mahvish Khan; Mohd Wajid Ali Khan; Irfan Ahmad Ansari (Frontiers in Pharmacology)
IntroductionDiabetic retinopathy is a significant microvascular disorder and the leading cause of vision impairment in working-age individuals. Hyperglycemia triggers retinal damage through mechanisms such as the polyol pathway and the accumulation of advanced glycation end products (AGEs). Inhibiting key enzymes in this pathway, aldose reductase (AR) and sorbitol dehydrogenase (SD), alongside preventing AGE formation, may offer therapeutic strategies for diabetic retinopathy and other vascular complications. This study investigates the ability of Ducrosia anethifolia, an Arabian plant, to inhibit AR and SD enzymes.MethodsMethanolic extracts of the plant were tested in enzyme assays and further analyzed using Lineweaver-Burk plots for kinetic insights. Additionally, the effects on AGE production and sorbitol accumulation in red blood cells were evaluated.ResultsThe methanolic extract showed strong inhibitory effects on AR (IC50: 69.41 ± 3.59 μg/mL) and SD (IC50: 31.11 ± 5.58 μg/mL), acting through a mixed-inhibition mechanism. It also significantly reduced sorbitol accumulation and AGE formation.DiscussionThese findings suggest that the extract’s inhibition of the polyol pathway enzymes is due to its phytochemical content. Further isolation and identification of these active compounds could provide valuable insights for developing future pharmaceutical treatments for diabetic retinopathy.